Integration of Computational Thinking in a Thermodynamics E-Module on the Ahmaddahlan.NET Website as an Effort to Strengthen Digital Literacy - Dirgah Kaso Sanusi; Ahmad Dahlan; M. Agus Martawijaya; Mahir Mahir (Pustaka Digital Indonesia, 2025)
The rapid advancement of digital technology necessitates learning materials that not only support instructional processes but also foster higher-order thinking skills among university students. This study aims to develop a Thermodynamics e-module grounded in computational thinking (CT) principles and integrated into the Ahmaddahlan.NET learning platform to enhance students’ digital literacy. The urgency for this development stems from the limitations of conventional thermodynamics instruction, which often struggles to connect fundamental concepts with empirical applications and computational analysis. As a result, an interactive, technology-based instructional approach is essential for improving students’ competency attainment. The research utilized the ADDIE Research and Development (R&D) framework, encompassing five stages: analysis, design, development, limited implementation, and evaluation. The e-module was designed around four core CT components decomposition, pattern recognition, abstraction, and algorithmic thinking. A limited trial was conducted with first-semester students enrolled in Basic Physics. Data were collected through expert validation and student response questionnaires assessing clarity, readability, and ease of access. Expert validation yielded a score of 95.1%, categorizing the e-module as highly feasible. In terms of practicality, user responses reached 88.1%, indicating that the interactive interface, intuitive navigation, and integration of digital content provided a positive learning experience. The module’s effectiveness was reflected in students’ digital literacy outcomes, which achieved a “good” category score of 79.8%, encompassing digital skills, digital security, digital culture, and digital ethics and responsibility. Overall, the findings demonstrate that the developed CT-based e-module effectively supports 21st-century learning demands and has strong potential as an innovative instructional resource in higher education settings. Its integration of computational thinking and digital literacy provides a robust foundation for modernizing thermodynamics instruction. The rapid advancement of digital technology necessitates learning materials that not only support instructional processes but also foster higher-order thinking skills among university students. This study aims to develop a Thermodynamics e-module grounded in computational thinking (CT) principles and integrated into the Ahmaddahlan.NET learning platform to enhance students’ digital literacy. The urgency for this development stems from the limitations of conventional thermodynamics instruction, which often struggles to connect fundamental concepts with empirical applications and computational analysis. As a result, an interactive, technology-based instructional approach is essential for improving students’ competency attainment. The research utilized the ADDIE Research and Development (R&D) framework, encompassing five stages: analysis, design, development, limited implementation, and evaluation. The e-module was designed around four core CT components decomposition, pattern recognition, abstraction, and algorithmic thinking. A limited trial was conducted with first-semester students enrolled in Basic Physics. Data were collected through expert validation and student response questionnaires assessing clarity, readability, and ease of access. Expert validation yielded a score of 95.1%, categorizing the e-module as highly feasible. In terms of practicality, user responses reached 88.1%, indicating that the interactive interface, intuitive navigation, and integration of digital content provided a positive learning experience. The module’s effectiveness was reflected in students’ digital literacy outcomes, which achieved a “good” category score of 79.8%, encompassing digital skills, digital security, digital culture, and digital ethics and responsibility. Overall, the findings demonstrate that the developed CT-based e-module effectively supports 21st-century learning demands and has strong potential as an innovative instructional resource in higher education settings. Its integration of computational thinking and digital literacy provides a robust foundation for modernizing thermodynamics instruction.